A Dark, Bare Rock for TOI-1685 b from a JWST NIRSpec G395H Phase Curve - Rafael Luque; Brandon Park Coy; Qiao Xue; Adina D. Feinstein; Eva-Maria Ahrer; Quentin Changeat; Michael Zhang; Sarah E. Moran; Jacob L. Bean; Edwin Kite; Megan Weiner Mansfield; Enric Pallé (The Astronomical Journal, 2025)
We report JWST NIRSpec/G395H observations of TOI-1685 b, a hot rocky super-Earth orbiting an M2.5V star, during a full orbit. We obtain transmission and emission spectra of the planet and characterize the properties of the phase curve, including its amplitude and offset. The transmission spectrum rules out clear H _2 -dominated atmospheres, while secondary atmospheres (made of water, methane, sulfur dioxide, or carbon dioxide) cannot be statistically distinguished from a flat line. The emission spectrum is featureless and consistent with a dark surface, ruling out carbon dioxide-, sulfur dioxide-, or methane-dominated atmospheres thicker than 100 mbar. Collecting all evidence, the properties of TOI-1685 b are consistent with a blackbody with no heat redistribution and a low albedo, with a dayside brightness temperature 0.99 ± 0.07 times that of a perfect blackbody in the NIRSpec NRS2 wavelength range (3.823–5.172 μ m). Our results add to the growing number of seemingly airless M-star rocky planets, thus constraining the location of the “Cosmic Shoreline.” Three independent data reductions have been carried out, all showing a high-amplitude correlated noise component in the white and spectroscopic light curves. The correlated noise properties are different between the NRS1 and NRS2 detectors—importantly, the timescales of the strongest components (4.5 hr and 2.5 hr, respectively)—suggesting the noise is from instrumental rather than astrophysical origins. We encourage the community to look into the systematics of NIRSpec for long time series observations.